PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN MASYARAKAT TERHADAP KEPUASAN MASYARAKAT DI KANTOR X - Slamet Riyanto; Titing Qomaryati (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2021)
This study aims to analyze and prove the effect of service quality and public trust on community satisfaction in office X. This type of research is an explanatory study with a cross sectional study approach. The research sample was 125 people with random sampling technique. The findings of this study indicate that there is a significant influence between service quality and community satisfaction. And there is a significant influence between public trust on public satisfaction of service users at office X.